Neutron Induced Reaction Dynamics, Using Dynamical Cluster Decay Model - Goyal, Komal (My University, 2011)
Neutron induced reaction dynamics have been studied using Dynamical Cluster Decay Model (DCM). The DCM based fission as well as neutron cross-sections find nice comparison with experimental data. It may be noted that DCM has been extensively applied for understanding the decay mechanism of nuclear systems formed in heavy ion reactions and its validity is checked in reference to neutron induced reactions for the first time here. The following reactions are worked upon over a wide range of incident energies. (i) 1n0+232Th233Thfission (ii) 1n0+233U234U232U+21n0 The work presented in this dissertation carries three chapters. CHAPTER 1 Chapter 1 consists of basics and overview of Accelerator Driven System (ADS). The utility of neutron induced reactions in reference to ADS and nuclear energy etc. is discussed in brief. CHAPTER 2 Chapter 2 consists of the description of Dynamical Decay Cluster Model (DCM). It gives the description of various potentials used in DCM along with other parameters of the model. The deformation effects of nuclear systems are included in the framework of DCM. CHAPTER 3 The details of DCM based calculations on 1n0+232Th233Thfission and 1n0+233U234U232U+21n0 reactions are discussed in chapter 3.
M.Sc. (Physics)
Keywords: Dynamical Cluster Decay Model